Orbital Apex Syndrome with Central Retinal Artery Occlusion Following Tooth Extraction - Chandana Chakraborti; Nabanita Barua; Rosy Chishti; Sheuli Kumar (Delhi Journal of Ophthalmology)
A 39-year-old male, known diabetic presented with drooping of upperlid and visual loss in the left eye (LE) along with pain in the eye and periorbital region. This was preceded by tooth extraction 2 days back. There was inaccurate projection of rays in the left eye along with complete ptosis, proptosis, relative afferent pupillary defect (RAPD) and limitations of ductions. Fundoscopy revealed features of papillitis with central retinal artery occlusion (CRAO). The examination of the right eye was within normal limits. Patient had high blood sugar levels. Contrast enhanced computed tomography (CECT) scan of brain and orbit was suggestive of left paranasal sinusitis. The clinical and the radiological findings were suggestive of orbital apex syndrome with central retinal artery occlusion of the left eye (LE). The case was managed conservatively with systemic antibiotics, non-steroidal anti-inflammatory drugs and injection human insulin. Pain, proptosis and conjunctival chemosis subsided within 2 days but other features remained static. Dentogenic cause of orbital apex syndrome is very rare. We intend to discuss clinical features and management of such case.